Certification, agricultural waste, organic production, herbal medicine and biotechnology in the conception of farmers of the State of Goiás - Sabrina Lucas Ribeiro Freitas; Lucas Andrade Mendes; Daniella Ferreira Cordeiro Gomes; Paulo José Bastos Queiroz; Rogério Elias Rabelo; Luiz Antônio Franco da Silva (Revista Ceres)
ABSTRACT The organic production system aims not at the intensive exploitation of resources, but the correct management of waste, the use of alternative treatments of animal diseases, and the utilization of some biotechnologies to assist in production. This is an exploratory study to evaluate the way farmers perceive the certification of their farms, the organic agricultural production, waste control, and the use of herbal medicine and biotechnologies in their properties. Fifteen farmers from the Dom Fernando Gomes dos Santos (GI) settlement, in Itaberaí, participated in the study, besides 15 farmers (GII) who are not participants in agrarian reform programs from different municipalities in the state of Goiás. Information was collected using questionnaires that addressed issues related to certification of farms, production of waste, organic agricultural production, herbal medicine, and biotechnology. Most farmers of GI and GII were unfamiliar with farm certification. Most GII farmers knew about agricultural waste, but few GI farmers knew its meaning. Most farmers of the two groups were familiar with the term organic agricultural production. More GII farmers were familiar with herbal medicines than GI. In both groups the term biotechnology was unknown to most people. It was concluded that this lack of knowledge by the majority of farmers about most topics presented shows the need to plan and execute actions to assist in the dissemination of information among farmers, settlers or not, using practical and functional strategies.